Evaluation of nutritional parameters of hemodialysis patients - Kaynar, k (SOCIETY OF "FRIENDS OF HIPPOKRATIA JOURNAL", 2012)
Background: This study was performed to investigate nutritional parameters of hemodialysis patients by using anthropometric and biochemical measurements. Methods: Data from the last 6 months of 22 adult hemodialysis patients with a mean age of 61 ± 14 years were analyzed retrospectively. Dialysis vintage, normalized protein catabolic rate (nPCR), serum biochemical parameters, mid arm muscle circumference (MAMC) were determined as mean and standard deviation. Correlations between the variables were computed by coefficient p of Pearson. Results: We found significant positive correlations: age of patients versus C-reactive protein, MAMC versus LDL-Cholesterol, MAMC versus body mass index, albumin versus hemoglobin. There were also significant negative correlations: age versus serum creatinine, age versus albumin, age versus intact parathyroid hormone (iPTH), dialysis vintage versus MAMC. Conclusion: In conclusion, age seem to be negatively associated with iPTH and albumin. As dialysis vintage increases, muscle mass seems to decrease.